How will the Patient Protection and Affordable Care Act affect liability insurance costs? - Auerbach, David I.; Heaton, Paul; Brantley, Ian (RAND Corporation, 2014)
"This report identifies potential mechanisms through which the Affordable Care Act (ACA) might affect liability claim costs and develops rough estimates of the size and direction of expected impacts as of 2016. Overall, effects of the ACA appear likely to be small relative to aggregate auto, workers' compensation, and medical malpractice insurer payouts, but some states and insurance lines may experience cost changes as high as 5 percent or more"--Publisher's description